2019
DOI: 10.1007/s40201-019-00421-7
|View full text |Cite
|
Sign up to set email alerts
|

Households’ behavior and social-environmental aspects of using bag dustbin for waste recovery in Tehran

Abstract: The suitable dustbin can cause a significant increase in household participation in separated dry waste at production source and recycling rate. This study was conducted on 100 households in Tehran for two weeks for households' wastes without any intervention. After two weeks, the tough-flexible bag dustbins were delivered to the families. At the next stage, by analysing the separated dry wastes by households, comparing the cost of new bag dustbin with plastic garbage bags, and completing some questionnaires, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This problem was raised in the stakeholder interviews and the low budget of the waste management organisation for training was cited as a reason for this. In other studies, door-to-door education was effective [ 55 , 58 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This problem was raised in the stakeholder interviews and the low budget of the waste management organisation for training was cited as a reason for this. In other studies, door-to-door education was effective [ 55 , 58 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 97%
“…Situational factors such as convenience tools can encourage residents to separate waste [ 51 ]. The study by Amanidaz et al found that the provision of facilities increased waste separation [ 58 ]. In Zhang's study, environmental factors were predictors of people's waste separation behaviour [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two interventions accounted for the largest sample sizes (1000 and 6580) [34,40]. However, in two studies the number of participants was less than 100 cases [50,53], and in three studies it was 100-102 participants [43,45,49]. Most studies had a volume of 144-680 subjects.…”
Section: Quantity Of Studiesmentioning
confidence: 96%
“…Burn [30] Haldeman [31] Schultz [32] Haldeman [31] Zhuang [33] Cotterill [34] Bryce [35] Cotterill [ Bryce [35] Karout [36] Lyas [37] Van der Werff [38] Del Cimmuto [39] Hoson [40] Karimi [41] Tong [42] 1997 Amanidaz [49] 2019 Iran…”
Section: Encouragementmentioning
confidence: 99%
See 1 more Smart Citation